Exploring the influence and effectiveness of block-based visual programming on self efficacy towards human resource students: a systematic review - Muhammad, Mohd Hilal; Mohd Zukhi, Mohd Zhafri; Che Sobry, Suheil; Nor A’zam, Muhammad Khairul Zharif; Hanafi, Ahmad Harith Ashrofie (Universiti Teknologi MARA, Kedah, 2025)
The aim of this paper is to measure the influence and effectiveness of block-based visual programming on self-efficacy towards social science students in the human resource domain using the block-based visual programming tools the MIT Apps Inventor. Programming skills can be exercised as a foundation for developing strong problem-solving skills, which are vital for both technical and non-technical students. A survey was conducted using questionnaires containing 24 items measuring the respondent’s self-efficacy. The reliability of the instruments recorded at the level of α = .912 was conducted on 53 respondents. The respondents of the study were 62 undergraduate social science students in human resources, selected based on a simple random sampling technique. The data collected were analyzed descriptively (frequency and percentage) and inference (mean analysis, t-test, and Pearson correlation coefficient - PCC). Overall, the findings report that the self-efficacy level of undergraduate social science students in human resources on block-based visual programming is high. The t-test analysis results indicate no significant difference in self-efficacy based on gender and the study background of the respondents. The correlation analysis also noted no self-efficacy relationship between computers in block-based visual programming and academic achievement. Research reveals that the level of self-efficacy of undergraduate social science students in human resources is relatively highly capable of providing alternative problem-solving skills using block-based visual programming.